Volume–outcome relationship of liver surgery: a nationwide analysis. Issue 7 (24th March 2020) - Olthof, P. B.; Elfrink, A. K. E.; Marra, E.; Belt, E. J. T.; van den Boezem, P. B.; Bosscha, K.; Consten, E. C. J.; den Dulk, M.; Gobardhan, P. D.; Hagendoorn, J.; van Heek, T. N. T.; IJzermans, J. N. M.; et al.
Abstract : Background: Evidence for an association between hospital volume and outcomes for liver surgery is abundant. The current Dutch guideline requires a minimum volume of 20 annual procedures per centre. The aim of this study was to investigate the association between hospital volume and postoperative outcomes using data from the nationwide Dutch Hepato Biliary Audit. Methods: This was a nationwide study in the Netherlands. All liver resections reported in the Dutch Hepato Biliary Audit between 2014 and 2017 were included. Annual centre volume was calculated and classified in categories of 20 procedures per year. Main outcomes were major morbidity (Clavien–Dindo grade IIIA or higher) and 30‐day or in‐hospital mortality. Results: A total of 5590 liver resections were done across 34 centres with a median annual centre volume of 35 (i.q.r. 20–69) procedures. Overall major morbidity and mortality rates were 11·2 and 2·0 per cent respectively. The mortality rate was 1·9 per cent after resection for colorectal liver metastases (CRLMs), 1·2 per cent for non‐CRLMs, 0·4 per cent for benign tumours, 4·9 per cent for hepatocellular carcinoma and 10·3 per cent for biliary tumours. Higher‐volume centres performed more major liver resections, and more resections for hepatocellular carcinoma and biliary cancer. There was no association between hospital volume and either major morbidity or mortality in multivariable analysis, after adjustment for known risk factors for adverse events. Conclusion: Hospital volume and postoperative outcomes were not associated. Abstract : This study analysed the association between hospital volume and postoperative outcomes in the nationwide Dutch Hepato Biliary Audit. A total of 5590 resections was performed across 34 centres with a median annual centre volume of 35 (i.q.r. 20–69) procedures. No association was found between hospital and postoperative outcomes. Cut‐off about right Abstract : Antecedentes: La asociación entre el volumen hospitalario y los resultados de la cirugía hepática no está clara. Según la recomendación actual de las guías holandesas se requiere un volumen mínimo de 20 procedimientos anuales por centro. El objetivo de este estudio fue analizar la asociación entre el volumen hospitalario con los resultados postoperatorios en la auditoría hepatobiliar obligatoria holandesa a nivel nacional. Métodos: Se realizó un estudio a nivel nacional en los Países Bajos. Se incluyeron todas las resecciones hepáticas registradas en la auditoría hepatobiliar holandesa entre 2014 y 2017. El volumen anual del centro se calculó y se clasificó en categorías de 20 procedimientos por año. Los objetivos principales fueron la morbilidad de mayor grado (Clavien‐Dindo grado IIIA o superior) y la mortalidad hospitalaria o la mortalidad a los 30 días. Resultados: Se realizaron un total de 5.590 resecciones en 34 centros con una mediana (rango intercuartílico) de volumen anual de 35 procedimientos (20‐69). La tasa global de morbilidad mayor fue del 11% y la mortalidad del 2%. La mortalidad fue de 1, 9% después de la resección por metástasis hepáticas colorrectales ( colorectal liver metastases, CRLM), 1, 2% para no CRLM, 0, 4% para tumores benignos, 4, 9% para carcinoma hepatocelular, y 10, 3% para tumores biliares. Los centros de mayor volumen realizaron más resecciones hepáticas mayores y más resecciones por carcinoma hepatocelular y cáncer biliar. En el análisis multivariable después de ajustar por factores de riesgo conocidos de eventos adversos, no se observó ninguna asociación entre el volumen hospitalario y la morbilidad o mortalidad mayor. Conclusión: No hubo asociación entre el volumen hospitalario y los resultados postoperatorios de la cirugía hepática en los Países Bajos.